PREVALENCE OF THEILERIA ANNULATA INFECTED HARD TICKS OF CATTLE AND BUFFALO IN PUNJAB, PAKISTAN - Z. Ali; A. Maqbool; K. Muhammad; M. S. Khan; M. Younis (Journal of Animal and Plant Sciences, 2013)
A study to investigate prevalence of theilleria infected hard ticks of dairy cattle and buffalo was carried out in Faisalabad, Jhang and Khanewal districts of Punjab, Pakistan. Ticks were collected during July and August, 2007 from infested dairy animals irrespetive of age, sex and weight. These animals were from 30 livestock farms, each having more than 25 animals (cattle and buffaloes). Six thousand two hundred and sixty three ticks were collected from 710 cattle and 320 buffaloes. Overall prevalence of Hyalomma species was significantly higher (61%) than that of other genera of hard ticks (p>0.05). In sex-wise distribution, it was found that female Hyalomma species were the highest (85%) followed by Amblyomma species (81%), while prevalence of Boophilus species and Haemaphysalis species were 77%. The ticks infestation rate in cattle (70%) was significantly higher than that of buffaloes (34%). PCR results showed that Theilleria annulata was detected in 50% Hyalomma anatolicum and 40% Hyalomma dromedary ticks. No theilerial organism was detected in Hyalomma marginatum, Boophilus annulatus and Amblyomma varigatum ticks.
Keywords: Prevalence; Buffaloes; Hard ticks; Livestock census